«Desde las orillas del río Guama...» - Gruzinski, Serge (2008)
After a tour offering us for his intense academic life developed between Europe and America, Gruzinsky raises the project of a global history, which includes aspects obviated for the history of the national states. The Spanish monarchy constitutes the first European globalization, where the Islam, the christianity and the idolatrous worships were interacting «to planetary scale and in a synchronous way». For this author, which is interested is to investigate the emergence of a world-conscience in the context of the globalization and its multiple transformations.